Plan de marketing para el posicionamiento de la empresa WINGO S.A en la ciudad de Quevedo periodo 2011 - Cobeña Rosado, Kerly Tatiana (2011)
The Marketing plan for the positioning of the company Wingo S.A. carried out in the Province of The Rivers, city of Quevedo in the year 2011, considering to be a universe the population of the canton Quevedo 167997 of which there was obtained a sample of 383 persons to polling and of 1936 Companies associated with the Chamber of Trade of Quevedo it was possible to obtain a sample of 321. The methods applied for the development of this investigation are: Inductivo. - Served to know the different parts of the problem and to establish the relations between the elements of the object of the investigation. Deductivo.- was in use for constructing the forecast of the positioning of the company Wingo S.A. in the city of Quevedo. Observation. - applied himself in order to analyze several aspects of the situation of the company. Encuesta. - carried out in order to obtain information and proved whose interpretation allowed to establish conclusions and recommendations chord to the royal situation of the company. The results obtained across the instrument applied to the companies associated with the Chamber of Trade of Quevedo and the population in general of Quevedo, was established by that: The company Merlin S.A. has 9 and 7 %, Milenium S.A. 16 and 7 % respectively, this information allowed to know that the company Wingo S.A. has an opportunity with regard to the competition. Also one determined that there exists a percentage of 64 % of companies associated with the Chamber of Trade of Quevedo and of 72 % of the population in general of Quevedo interested in contracting the services of a company specialized in cleanliness. Likewise it is possible to think that the offer is viable to realize the marketing plan for the positioning of the company Wingo S.A., proposed that it includes a promotional plan with an advertising campaign. Finally one presents an offer to create a marketing plan for the positioning of the company Wingo S.A. proposing a promotional plan with an advertising campaign.